ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL DENGAN MODEL INDEKS TUNGGAL PADA SAHAM-SAHAM INDEKS KOMPAS 100 DI BURSA EFEK INDONESIA PERIODE FEBRUARI 2016- JANUARI 2019 - Tandirerung Ranteallo, Asrah; Herawati, Niken (EDUTECH CONSULTANT, 2019)
Abstract This study aims to analyze the construction of the optimal portfolio with the single index model on stocks Kompas 100 Index in the Indonesia Stock Exchange.The research methodology used is descriptive qualitative with panel and secondary data obtained from the Indonesian Stock Exchange. Technical sampling method used is purposive sampling method with data during the period of February 2016 to the period of January 2019. The data analysis technique used is portfolio analysis using single index model.The result of this study indicates that the optimal portfolio proportion is achieved by the proportion of stocks in Kompas 100 Index such as PTPP (33.29%), AISA (18.54%), BJBR (17.76%), TBIG (15.43%), JPFA (6.92%), LPCK (4.32%), DILD (1.56%), SMRA (1.12%) and CTRA (1.06%). The optimal result of expected return and risk is obtained by stocks in Kompas 100 Index, the daily expected return of 0.141% and daily risk of 0,012%. The result of the comparison on diversification benefit between Individual and Kompas 100 Index, is that the diversification profits generated by Kompas 100 Index have more variants of better profit compared to profit diversification of Individual Investment.